2021
DOI: 10.3390/jrfm14070336
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evidence Regarding the Impact of Economic Growth and Inflation on Economic Sentiment and Household Consumption

Abstract: The dynamics of the interconnected global market and consumption behavior has recently changed considerably. Using a sample of 28 nations within the European Union, the study examined the degree to which economic growth and inflation impacted economic sentiment and household consumption during the time frame of December 2019 up to October 2020. The results estimated via panel generalized method of moments and panel least squares (with cross-section weights, time fixed effects) showed that economic sentiment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In any case, the fact that there is a higher concentration of variable values far from the mean (tails), together with a lower This explains the shape of the frequency/probability distribution, which demonstrates thicker tails, a sharper center, and a lower proportion of intermediate values between the peak and tails. In order to detect possible multicollinearity in the variables, we used the variance inflation factor (VIF) following Batrancea (2021a) and L. M. Batrancea (2021b). The VIF calculations can be found in the Appendix, as Table A.2.…”
Section: Resultsmentioning
confidence: 99%
“…In any case, the fact that there is a higher concentration of variable values far from the mean (tails), together with a lower This explains the shape of the frequency/probability distribution, which demonstrates thicker tails, a sharper center, and a lower proportion of intermediate values between the peak and tails. In order to detect possible multicollinearity in the variables, we used the variance inflation factor (VIF) following Batrancea (2021a) and L. M. Batrancea (2021b). The VIF calculations can be found in the Appendix, as Table A.2.…”
Section: Resultsmentioning
confidence: 99%
“…It shows that over the period under review the consumption bundles of the poorest components of the EU population increased by 11.2%, which caused the Gini indicator to change by 0.04 points. Another author such (Batrancea, 2021) draws attention to changes in consumption behavior as a result of the latest global developments. The analysis covers the EU28 and aims to quantify the impact of economic growth and inflation on ESI and household consumption between December 2019 and October 2020.…”
Section: Prices and Inflationmentioning
confidence: 99%
“…Multiple studies have shown that inflation and oil prices positively impact the growth rate of different nations (Uddin, 2021;Jassim et al, 2021;Dinh, 2020). Several studies have shown a negative correlation between oil prices and inflation rates (Xia, 2021;Batrancea, 2021;Helali et al, 2021). Several studies point to an asymmetric effect (Rumbia et al, 2020;Chugunov et al, 2021).…”
Section: Literature Review On the Impact Of Industrial Value-added An...mentioning
confidence: 99%